2012
DOI: 10.1007/s11250-012-0098-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different finishing systems on carcass traits, fatty acid composition, and beef quality characteristics of young Eastern Anatolian Red bulls

Abstract: The effects of three finishing systems on carcass composition and other characteristics of meat were studied in 15 young Eastern Anatolian Red bulls in Eastern Turkey. For 93 days, five bulls grazed pasture (P), five grazed the same pasture and were given concentrate supplementation (P + C), and five grazed the same pasture for 93 days, and then for an additional 40 days, they received concentrate in a barn (PF). Carcasses of the P bulls were lighter and leaner than those of the PF animals. Compared with the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
1
14
5
Order By: Relevance
“…The finding differs from the results reported by Barham et al [15]. They are lower than values reported by Hollao et al [7], and are higher than those reported by Yüksel et al [9] and Yüksel et al [11]. Hot carcass, edible meat, and pelvic fat are interrelated.…”
Section: Discussioncontrasting
confidence: 68%
“…The finding differs from the results reported by Barham et al [15]. They are lower than values reported by Hollao et al [7], and are higher than those reported by Yüksel et al [9] and Yüksel et al [11]. Hot carcass, edible meat, and pelvic fat are interrelated.…”
Section: Discussioncontrasting
confidence: 68%
“…Recently, Alfaia et al (2009) andYüksel et al (2012) studied the effect of the use of concentrate before slaughter, in young bulls raised to the pasture, on meat quality. However, there are some differences with our experiment.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some differences with our experiment. In the trial of Yüksel et al (2012) the bulls were transferred in a feedlot and fed with concentrate 40 days before being slaughtered (in our trial 60 days before slaughtering), whereas in the experiment of Alfaia et al (2009) the animals were slaughtered at different times and therefore at different ages (in our experiment all the bulls were slaughtered at the same age). Moreover, considering the importance that Podolian breed holds in supporting of socio-economic development of marginal areas such as the South of Italy, we wanted to verify the effect of this strategy on meat quality of this native breed.…”
Section: Introductionmentioning
confidence: 99%
“…More information has recently become available on fatty acid composition and mineral and vitamin concentrations in different muscles from various breeds and under different production systems (Faucitano et al, 2008;Leheska et al, 2008;Purchas and Zou, 2008;Warren et al, 2008;De la Fuente et al, 2009;Duckett et al, 2009;Daley et al, 2010;Schonfeldt et al, 2010;Pordomingo et al, 2012;Sexten et al, 2012;Yuksel et al, 2012); however, little information is available regarding other components in beef that have been reported to be related to human health. Because of their potential protective effects, these components are generally referred to as bioactive compounds, or health-promoting active ingredients (Muller et al, 2002;Wyss et al, 2007;Hipkiss, 2009).…”
Section: Introductionmentioning
confidence: 99%